Porous sucker with gradient distribution of pores and preparation method of porous sucker
Through the preparation method of porous suction cups with pore gradient distribution, the problem that existing porous alumina porous suction cups cannot meet the adsorption force requirements in different parts in specific occasions is solved, and the pore gradient controllable and adsorption effect is maximized, which is suitable for a wider application needs.
Patent Information
- Application Number
- CN202510086595.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
Smart Images

Figure CN119912273A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of suction cups, and more specifically, to a porous suction cup with a pore gradient distribution and a preparation method thereof. Background Art
[0002] Alumina porous ceramics are environmentally friendly ceramics. Due to their porous microstructure, they have a large specific surface area and porosity, thus having excellent adsorption and permeability properties. These properties enable them to play an important role in high-tech fields such as semiconductor manufacturing, and are of great significance to reducing production costs and improving the competitiveness of domestic manufacturing.
[0003] Although there are many ways to produce porous alumina suction cups on the market, the adsorption performance of these products is generally single and uniform, and there are still some deficiencies for the needs of some specific occasions, such as the problem that wafers are easily deformed during handling and processing due to insufficient edge adsorption. The adsorption force generated by the material is related to the porosity of the material itself. Under the same negative pressure, the larger the pore size and the higher the porosity of the material, the greater the adsorption force generated. Therefore, it is urgent to find a method to control the porosity and pore size gradient distribution of different regions of the material to meet the adsorption force requirements of the product at different positions in actual applications. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that the current single-pore suction cup cannot meet the different adsorption force requirements of different parts for some specific occasions. The present invention provides a method for preparing a porous suction cup with a pore gradient distribution, which has a simple process, controllable pore gradient distribution, low cost and a pore gradient distribution.
[0005] The present invention provides a method for preparing a porous suction cup with a pore gradient distribution, comprising the following steps:
[0006] (1) Formula powder mixing:
[0007] 70-90wt% of low-activity alumina powder (particle size 10-60μm), 0-15wt% of high-activity alumina powder (particle size 0.1-1.5μm), 0-15wt% of liquid-phase sintering aid, and 0-30wt% of pore-forming agent are ball-milled to obtain a formula powder for granulation;
[0008] The high-activity alumina powder will first be dissolved with the additive to form a liquid phase, while inhibiting the growth of low-activity alumina grains or solid dissolving to form a liquid phase, thereby protecting the large-grain alumina skeleton and improving the material strength.
[0009] The sintering activity of alumina powder is related to the powder particle size, specific surface area and crystal phase. The specific surface area is usually related to the powder particle size to a certain extent. Here it is mainly characterized by the powder grain size. The particle size of ten microns or more is low-activity alumina, while the particle size of tens of nanometers to several microns is active alumina.
[0010] In the formula powder of the present application, high-activity and low-activity alumina powders are used together, with the purpose of using large-particle (particle size of 10-60μm) low-activity alumina as the skeleton to ensure uniform pore distribution and interconnection. However, relying solely on sintering between large grains to maintain the structure of the green body is prone to problems such as low green body strength and easy cracking and slagging. Therefore, it is necessary to form a liquid phase connection between large-particle low-activity alumina through the action of a liquid phase auxiliary agent with high-activity alumina to increase the strength of the green body. In addition, high-activity alumina has a small particle size (particle size of 0.1-1.5μm) and a larger specific surface energy, which makes it easier to form a liquid phase, which can protect the low-activity alumina to a certain extent and prevent large-particle alumina from further growing under the action of the auxiliary agent.
[0011] Preferably, the step (1) is specifically as follows: firstly add high-activity alumina powder, liquid-phase sintering aid, and spherical pore-forming agent, and then ball-mill and mix for 4-8 hours, and then add large-particle α-phase low-activity alumina powder and continue ball-milling for 12-24 hours.
[0012] More preferably, the low-activity alumina powder is α-phase low-activity alumina with a particle size of 10-60 μm; the high-activity alumina has a purity of 99.95% or more and a median particle size of 0.1-1.5 μm; the liquid-phase sintering aid used is at least one of silicon dioxide, titanium dioxide, and zirconium oxide powders with AR grade purity and a particle size of 1-10 μm; the pore-forming agent used is paraffin micropowder and / or PMMA micropowder with a particle size of 7.5-50 μm.
[0013] More preferably, in step (1), the ball ratio of the ball to the ball is 1:1.5-1:2.5, wherein the ball milling medium is 99 alumina balls, and the ball milling speed is 70-90 r / min.
[0014] Among them, silicon dioxide, titanium dioxide and activated alumina form a solid solution to promote sintering and reduce the sintering temperature at the same time. Zirconia as other phases can inhibit further abnormal growth of grains and improve the uniformity of pore dispersion. Moreover, all additives used are oxides, and there is no need to increase the oxygen concentration for oxidation.
[0015] (2) Powder granulation with glue:
[0016] Add a binder to the formula powder and mix by ball milling to obtain a slurry, age and homogenize for a period of time, then dry and dehydrate, crush and sieve to obtain the final molding powder;
[0017] Specifically, in the step (2), the binder used is a PVA solution with a concentration of 10-15wt%, wherein the PVA has a viscosity of 40-55mPa·s, a degree of alcoholysis of 88%, and a molecular weight of 101200-110000. Since the original formula powders used are all lean powders with poor molding performance, the molding performance and uniformity of the powders can be improved by adding glue to the powders for granulation, thereby increasing the strength of the green body.
[0018] Preferably, in step (2), the amount of PVA solution added is 10-20wt% of the powder mass, the ball ratio of the ball mill is 1:1.5-1:3, the ball milling medium is zirconia ball, the particle size ratio is 1:1-2:1, the small ball diameter is 5-10mm, and the large ball diameter is 15-30mm.
[0019] More preferably, in the step (2), the slurry aging time is 24-48h, the ambient temperature is 20-40°C, and it is dehydrated and dried in a constant temperature and humidity drying oven at 40-60°C and 80-95% humidity for 3-12h. The residual moisture content in the final powder is controlled at 3-7%, the glue content is 1-3%, and the powder crushing particle size D50≤150μm and D90≤200μm.
[0020] (3) Dry pressing preforming:
[0021] The two prepared powders are dry pressed into disc-shaped and annular green bodies with nearly consistent green body thickness and density. The internal structure of the green bodies is relatively loose to a certain extent, and there is still room for further compression.
[0022] In the step (3), the dry pressing preforming pressure is 15-30 MPa, the thickness of the two powder preforms is 15-22 mm and the thickness difference does not exceed 0.2 mm, and the green density is 1.39-1.67 / cm 3 .
[0023] Specifically, the outer diameter of the inner cavity of the disc-shaped dry pressing mold is 150-170 mm, and the outer diameter of the inner cavity of the annular mold is 240-270 mm and the inner diameter is 150.2-170.2 mm.
[0024] (4) Secondary cold isostatic pressing:
[0025] The preformed green body is transferred into a rubber mold for assembly and sealing, and then the upper and lower end surfaces are fixed with metal clamps, and the green body is placed in a cold-pressed cylinder for secondary cold-pressing to obtain a green body;
[0026] In the step (4), the secondary cold isotropic pressure is between 180-260 MPa, the outer diameter of the inner cavity of the rubber mold is between 240.4-270.4 mm, the thickness of the metal clamping plate used is between 20-35 mm and the material is aluminum alloy, and the density of the green billet after cold is between 1.88-2.17 g / cm 3 .
[0027] At this time, the dry-pressed preformed green body is further compressed and densified, and the uncompacted powders in the contact parts between the preformed green bodies with different raw material ratios will mesh with each other during the further compression process to form a whole, and finally realize the composite molding of green bodies with multiple porosity formulas. The porosity and pore size between the inner and outer circles or different regions of the green body after sintering can be controlled by adjusting the ratio of the powder porosity formula used in the inner and outer circles or different regions of the green body.
[0028] The present application first performs dry pressing preforming and then cold isostatic pressing to achieve integrated regional molding of powders with various formulas, and the porosity and pore size of each region of the green body can be controlled by adjusting the powder formula ratio of each region.
[0029] (5) Debinding and sintering:
[0030] The sintering process adopted is a debinding-sintering integrated method. The blank is placed in a sintering furnace for sintering. The sintering temperature is 1500-1550℃ and the heat preservation time is 120-180min. Compared with some other alumina sintering processes, the required sintering temperature is relatively low, which can save costs to a certain extent.
[0031] Specifically, the sintering temperature of the sintering curve in step (5) is 1500-1550°C, and the heating curve is a sintering process curve: room temperature is increased to 100°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 200°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 250°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 350°C at 0.25-0.35°C / min and kept warm for 120-180min, then increased to 350°C at 0.25-0.35°C / min and kept warm for 120-180min, and then increased to 200°C at 0.25-0.5°C / min and kept warm for 150-200min. .5℃ / min to 450℃ and keep warm for 120-180min, then 0.25-0.5℃ / min to 600℃ and keep warm for 120-180min, then 1-1.5℃ / min to 900℃ and keep warm for 60-90min, then 1-1.5℃ / min to 1200℃ and keep warm for 60-90min, then 1-1.5℃ / min to 1400℃ and keep warm for 60-90min, then 1-1.5℃ / min to 1500-1550℃ and keep warm for 120-240min, then cool with the furnace.
[0032] (6) Finishing:
[0033] The sintered ceramic green body is placed in clarified low-temperature molten paraffin for pore sealing, and then dewaxed through subsequent processing to obtain the final product.
[0034] The molten paraffin has a relatively low melting point, is easy to clean and remove, is inert and non-corrosive, and has low strength that will not damage the internal pore structure of the blank. It has a good sealing effect on the sintered ceramic green body.
[0035] A porous suction cup with a pore gradient distribution is prepared by the preparation method of the porous suction cup with a pore gradient distribution. The inner and outer ring porosities of the porous suction cup are regulated in a stepwise manner within the range of 15-50% and the pore diameters are regulated within the range of 10-100 μm.
[0036] Compared with the prior art, the beneficial effects of the embodiments of the present application are as follows: compared with other existing single-pore-diameter porous suction cups that cannot meet the greater adsorption force required for specific parts, the porous suction cup with a pore gradient distribution prepared by the method of the present invention has the advantages of controllable pore gradient and maximizing the adsorption effect. Under the same negative pressure conditions, the higher the porosity of the material and the larger the pore size, the greater the adsorption force generated. By forming a plurality of formula powders in different regions into one piece, the content of the pore-forming agent in the formula and the particle size of the low-activity alumina are gradually adjusted from the inner circle to the outer circle, thereby achieving control of the porosity and pore size of each region of the green body after sintering. The porosity of the inner and outer circles of the suction cup can be step-controlled within the range of 15-50% and the pore size within the range of 10-100μm, thereby avoiding the problem of easy deformation of the wafer edge due to insufficient edge adsorption force, thereby making it suitable for a wider range of application needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0038] Figure 1 A schematic flow chart of a method for preparing a porous suction cup with a pore gradient distribution provided in an embodiment of the present application.
[0039] Figure 2 This is a scanning electron microscope image of the porous sample area prepared by using 80g of pore-forming agent with a particle size D50 of 30μm and α-phase low-activity alumina with a particle size D50 of 30μm. DETAILED DESCRIPTION
[0040] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. In the following embodiments, if there is no special description of the raw materials or processing technology, it is shown that the conventional commercially available raw material products or conventional processing technologies used in the art are used.
[0041] Example 1
[0042] This embodiment provides a method for preparing a porous suction cup with a pore gradient distribution, comprising the following steps:
[0043] (1) Formula powder mixing
[0044] Weigh 800 g of α-phase low-activity alumina with a particle size D50 of 30 μm, 100 g of high-activity alumina powder with a D50 of 0.4 μm, and 100 g of liquid-phase sintering aid (silicon dioxide) according to the mass ratio. Without adding a pore-forming agent, use 99 alumina balls to ball mill the mixture at a speed of 80 r / min and a material-ball ratio of 1:2 for 18 hours to obtain the formula powder used for granulation.
[0045] (2) Powder granulation with glue
[0046] Add 20% PVA solution (15wt%) of the powder mass to the above formula powder, ball mill at 25°C for 24 hours at a material-ball ratio of 1:2 (the ratio of 8mm small balls to 25mm large balls is 1:1), age at room temperature for 24 hours, dry in a constant temperature and humidity chamber at 48°C and 90% humidity for 6 hours, and crush to obtain molding powder A;
[0047] Weigh 800 g of α-phase low-activity alumina with a particle size D50 of 30 μm, 100 g of high-activity alumina powder with a particle size D50 of 0.4 μm, 100 g of liquid-phase sintering aid (silicon dioxide), and 40 g of pore-forming agent with a particle size D50 of 30 μm according to the mass ratio, and obtain molding powder B according to the same granulation steps;
[0048] Weigh 800 g of α-phase low-activity alumina with a particle size D50 of 30 μm, 100 g of high-activity alumina powder with a particle size D50 of 0.4 μm, 100 g of liquid-phase sintering aid (silicon dioxide), and 80 g of pore-forming agent with a particle size D50 of 30 μm according to the mass ratio, and obtain molding powder C according to the same granulation steps;
[0049] Weigh 800 g of α-phase low-activity alumina with a particle size D50 of 30 μm, 100 g of high-activity alumina powder with a particle size D50 of 0.4 μm, 100 g of liquid-phase sintering aid (silicon dioxide), and 120 g of pore-forming agent with a particle size D50 of 30 μm according to the mass ratio, and obtain molding powder D according to the same granulation steps;
[0050] Weigh 800 g of α-phase low-activity alumina with a particle size D50 of 30 μm, 100 g of high-activity alumina powder with a particle size D50 of 0.4 μm, 100 g of liquid-phase sintering aid (silicon dioxide), and 160 g of pore-forming agent with a particle size D50 of 30 μm according to the mass ratio, and obtain molding powder E according to the same granulation steps;
[0051] Among them, the residual moisture content of powder A is 6.2%, and the glue content is 2.8%; the residual moisture content of powder B is 6.2%, and the glue content is 2.7%; the residual moisture content of powder C is 6.3%, and the glue content is 2.9%; the residual moisture content of powder D is 6.4%, and the glue content is 2.9%; the residual moisture content of powder E is 6.4%, and the glue content is 2.7%.
[0052] (3) Dry pressing preforming
[0053] According to the above dry pressing preforming work, five kinds of powders are preformed at a pressure of about 14MPa. The size of the preformed green body A is D100.0*16.2, and the green body density is 1.65g / cm 3 The size of preformed green body B is D140-D100.1*16.2, and the green body density is 1.64g / cm 3 The size of the preformed green body C is D180-D140.2*16.2, and the green body density is 1.62g / cm 3 The preformed green body D size is D220-D180.2*16.2, and the green body density is 1.59g / cm 3 The preformed green body E size is D260-D220.2*16.2, and the green body density is 1.57g / cm 3 .
[0054] (4) Secondary cold isostatic pressing
[0055] The preformed blanks were assembled and then cold-formed at 240 MPa to obtain a green blank. The overall green density was 2.16 g / cm 3 .
[0056] (5) Debinding sintering
[0057] The porous alumina suction cup material with pore gradient distribution was sintered at 1550°C after debinding and sintering. The heating curve was as follows: room temperature was increased by 0.5°C / min to 100°C and kept for 200min, then increased by 0.5°C / min to 200°C and kept for 200min, then increased by 0.5°C / min to 250°C and kept for 200min, then increased by 0.35°C / min to 350°C and kept for 180min, then increased by 0.5°C / min to 450°C and kept for 120min, then increased by 0.5°C / min to 600°C and kept for 120min, then increased by 1°C / min to 900°C and kept for 60min, then increased by 1°C / min to 1200°C and kept for 60min, then increased by 1°C / min to 1400°C and kept for 60min, then increased by 1°C / min to 1550°C and kept for 180min and then cooled with the furnace.
[0058] (6) Finishing
[0059] The sintered ceramic green body is placed in clarified 58°C low-temperature molten paraffin for pore sealing, and then dewaxed through subsequent processing to obtain the final product.
[0060] The porosity of the finished product center A area is measured to be 18%, the pore size is 30-100μm, and the density is 3.07g / cm 3 The porosity of region B is 21%, the pore size is 40-100 μm, and the density is 2.96 g / cm 3 The porosity of region C is 25%, the pore size is 40-100 μm, and the density is 2.81 g / cm 3 The porosity of region D is 29.5%, the pore size is 50-100 μm, and the density is 2.64 g / cm 3 The porosity of region D is 35%, the pore size is 50-100 μm, and the density is 2.45 g / cm 3 .
[0061] Example 2
[0062] This embodiment provides a method for preparing a porous suction cup with a pore gradient distribution, comprising the following steps:
[0063] (1) Formula powder mixing
[0064] Weigh 900g of α-phase low-activity alumina with a particle size D50 of 15μm, 50g of high-activity alumina powder with a D50 of 0.6μm, 50g of liquid-phase sintering aid (titanium dioxide) and 40g of pore-forming agent with a D50 of 15μm (paraffin powder) according to the mass ratio, and use 99 alumina balls to ball mill the mixture at a speed of 70r / min and a material-ball ratio of 1:2 for 21 hours to obtain the formula powder used for granulation.
[0065] (2) Powder granulation with glue
[0066] Add 20% PVA solution (15wt%) of the powder mass to the above formula powder, ball mill for 36 hours at 25°C with a material-ball ratio of 1:2 (the ratio of 8mm small balls to 25mm large balls is 1:1), age at room temperature for 24 hours, dry in a constant temperature and humidity chamber at 48°C and 90% humidity for 6 hours, and crush to obtain molding powder A;
[0067] 900 g of α-phase low-activity alumina with a particle size D50 of 15 μm, 50 g of high-activity alumina powder with a particle size D50 of 0.6 μm, 50 g of liquid-phase sintering aid (titanium dioxide) and 80 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder B was obtained by the same granulation steps;
[0068] 900 g of α-phase low-activity alumina with a particle size D50 of 15 μm, 50 g of high-activity alumina powder with a particle size D50 of 0.6 μm, 50 g of liquid-phase sintering aid (titanium dioxide) and 120 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder C was obtained by the same granulation steps;
[0069] 900 g of α-phase low-activity alumina with a particle size D50 of 15 μm, 50 g of high-activity alumina powder with a particle size D50 of 0.6 μm, 50 g of liquid-phase sintering aid (titanium dioxide) and 160 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder D was obtained by the same granulation steps;
[0070] 900 g of α-phase low-activity alumina with a particle size D50 of 15 μm, 50 g of high-activity alumina powder with a particle size D50 of 0.6 μm, 50 g of liquid-phase sintering aid (titanium dioxide) and 200 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder E was obtained by the same granulation steps;
[0071] Among them, the residual moisture content of powder A is 5.9%, and the glue content is 2.6%; the residual moisture content of powder B is 5.7%, and the glue content is 2.7%; the residual moisture content of powder C is 5.8%, and the glue content is 2.6%; the residual moisture content of powder D is 5.6%, and the glue content is 2.9%; the residual moisture content of powder E is 6.0%, and the glue content is 2.8%.
[0072] (3) Dry pressing preforming
[0073] According to the above dry pressing preforming work, five kinds of powders are preformed at a pressure of about 18MPa. The size of the preformed green body A is D100.0*16.2, and the green body density is 1.65g / cm 3 The size of preformed green body B is D140-D100.1*16.2, and the green body density is 1.64g / cm3. The size of preformed green body C is D180-D140.2*16.2, and the green body density is 1.62g / cm3 The preformed green body D size is D220-D180.2*16.2, and the green body density is 1.59g / cm 3 The preformed green body E size is D260-D220.2*16.2, and the green body density is 1.57g / cm 3 .
[0074] (4) Secondary cold isostatic pressing
[0075] The preformed blanks were assembled and then cold-formed at 260 MPa to obtain a green blank. The overall green density was 2.16 g / cm 3 .
[0076] (5) Debinding sintering
[0077] The alumina porous suction cup material with pore gradient distribution was sintered at 1500°C after debinding and sintering. The heating curve was as follows: room temperature was increased by 0.5°C / min to 100°C and kept for 200min, then increased by 0.5°C / min to 200°C and kept for 200min, then increased by 0.5°C / min to 250°C and kept for 200min, then increased by 0.35°C / min to 350°C and kept for 180min, then increased by 0.5°C / min to 450°C and kept for 120min, then increased by 0.5°C / min to 600°C and kept for 120min, then increased by 1°C / min to 900°C and kept for 60min, then increased by 1°C / min to 1200°C and kept for 60min, then increased by 1°C / min to 1400°C and kept for 60min, then increased by 1°C / min to 1500°C and kept for 180min and then cooled with the furnace.
[0078] (6) Finishing
[0079] The sintered ceramic green body is placed in clarified 58°C low-temperature molten paraffin for pore sealing, and then dewaxed through subsequent processing to obtain the final product.
[0080] The porosity of the finished product center A area is 19%, the pore size is 10-50μm, and the density is 3.11g / cm 3 The porosity of region B is 22%, the pore size is 10-60 μm, and the density is 2.99 g / cm 3 The porosity of region C is 27%, the pore size is 20-70 μm, and the density is 2.80 g / cm 3 The porosity of region D is 32%, the pore size is 20-70 μm, and the density is 2.61 g / cm 3 The porosity of region D is 36%, the pore size is 20-80 μm, and the density is 2.46 g / cm 3 .
[0081] Example 3
[0082] This embodiment provides a method for preparing a porous suction cup with a pore gradient distribution, comprising the following steps:
[0083] (1) Formula powder mixing
[0084] 750 g of α-phase low-activity alumina with a particle size D50 of 60 μm, 150 g of high-activity alumina powder with a particle size D50 of 1 μm, and 100 g of a liquid-phase sintering aid (silicon dioxide: titanium dioxide: zirconium oxide = 2:2:1) were weighed according to the mass ratio, without adding a pore-forming agent;
[0085] First add high-activity alumina powder, liquid-phase sintering aid, and spherical pore-forming agent, and use 99 alumina balls to ball-mill for 8 hours at a speed of 90r / min and a material-ball ratio of 1:2.5. Then add large-particle α-phase low-activity alumina powder and continue ball-milling for 16 hours to obtain the formula powder used for granulation.
[0086] (2) Powder granulation with glue
[0087] 15% PVA solution (12 wt%) of the powder mass was added to the above formula powder, and ball milled at 25°C for 30 h at a material-ball ratio of 1:2 (the ratio of 8 mm small balls to 25 mm large balls was 1:1), aged at room temperature for 24 h, dried in a constant temperature and humidity chamber at 48°C and 85% humidity for 5 h, and crushed to obtain molding powder A;
[0088] 750 g of α-phase low-activity alumina with a particle size D50 of 60 μm, 150 g of high-activity alumina powder with a particle size D50 of 1 μm, 100 g of liquid-phase sintering aid (silicon dioxide: titanium dioxide: zirconium oxide = 2:2:1), and 40 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder B was obtained by the same granulation steps;
[0089] 750 g of α-phase low-activity alumina with a particle size D50 of 60 μm, 150 g of high-activity alumina powder with a particle size D50 of 1 μm, 100 g of liquid-phase sintering aid (silicon dioxide: titanium dioxide: zirconium oxide = 2:2:1), and 80 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder C was obtained by the same granulation steps;
[0090] 750 g of α-phase low-activity alumina with a particle size D50 of 60 μm, 150 g of high-activity alumina powder with a particle size D50 of 1 μm, 100 g of liquid-phase sintering aid (silicon dioxide: titanium dioxide: zirconium oxide = 2:2:1), and 120 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder D was obtained by the same granulation steps;
[0091] 750 g of α-phase low-activity alumina with a particle size D50 of 60 μm, 150 g of high-activity alumina powder with a particle size D50 of 1 μm, 100 g of liquid-phase sintering aid (silicon dioxide: titanium dioxide: zirconium oxide = 2:2:1), and 160 g of pore-forming agent (PMMA powder) with a particle size D50 of 15 μm were weighed according to the mass ratio, and the molding powder E was obtained by the same granulation steps;
[0092] Among them, the residual moisture content of powder A is 6.0%, and the glue content is 2.7%; the residual moisture content of powder B is 6.1%, and the glue content is 2.6%; the residual moisture content of powder C is 6.2%, and the glue content is 2.8%; the residual moisture content of powder D is 6.3%, and the glue content is 2.9%; the residual moisture content of powder E is 6.3%, and the glue content is 2.8%.
[0093] (3) Dry pressing preforming
[0094] According to the above dry pressing preforming work, five kinds of powders are preformed at a pressure of about 16MPa. The size of the preformed green body A is D100.0*16.2, and the green body density is 1.65g / cm 3 The size of preformed green body B is D140-D100.1*16.2, and the green body density is 1.63g / cm 3 The size of the preformed green body C is D180-D140.2*16.2, and the green body density is 1.61g / cm 3 The preformed green body D size is D220-D180.2*16.2, and the green body density is 1.58g / cm 3 The preformed green body E size is D260-D220.2*16.2, and the green body density is 1.56g / cm 3 .
[0095] (4) Secondary cold isostatic pressing
[0096] The preformed blanks were assembled and cold-formed at 250 MPa to obtain a green blank. The overall green density was 2.16 g / cm 3 .
[0097] (5) Debinding sintering
[0098] The porous alumina suction cup material with pore gradient distribution was sintered at 1550°C after debinding and sintering. The heating curve was as follows: room temperature was increased to 100°C at 0.25°C / min and kept warm for 150min, then increased to 200°C at 0.25°C / min and kept warm for 180min, then increased to 250°C at 0.25°C / min and kept warm for 150min, then increased to 350°C at 0.35°C / min and kept warm for 150min, then increased to 450°C at 0.5°C / min and kept warm for 150min, then increased to 600°C at 0.5°C / min and kept warm for 150min, then increased to 900°C at 1.5°C / min and kept warm for 90min, then increased to 1200°C at 1.5°C / min and kept warm for 90min, then increased to 1400°C at 1.5°C / min and kept warm for 90min, then increased to 1500°C at 1.5°C / min and kept warm for 200min and then cooled with the furnace.
[0099] (6) Finishing
[0100] The sintered ceramic green body is placed in clarified 58°C low-temperature molten paraffin for pore sealing, and then dewaxed through subsequent processing to obtain the final product.
[0101] The porosity of the finished product center A area is 19%, the pore size is 30-100μm, and the density is 3.11g / cm 3 The porosity of region B is 21.5%, the pore size is 40-100 μm, and the density is 2.99 g / cm 3 The porosity of region C is 25.5%, the pore size is 40-100 μm, and the density is 2.85 g / cm 3 The porosity of region D is 29.8%, the pore size is 50-100 μm, and the density is 2.66 g / cm 3 The porosity of region D is 35.61%, the pore size is 50-100 μm, and the density is 2.65 g / cm 3 .
[0102] Figure 2 This is a scanning electron microscope image of a porous sample area prepared by using α-phase low-activity alumina with a particle size D50 of 30 μm and 80 g of a pore-forming agent with a particle size D50 of 30 μm. Figure 2 It can be seen that the pore connectivity of the material is relatively uniform, and the pore size of the sample in the figure is around 20-80μm.
[0103] The beneficial effect of the above-mentioned implementation method is that the porous suction cup with pore gradient distribution prepared by the method of the present invention has the advantages of controllable pore gradient and maximizing the adsorption effect. Under the same negative pressure conditions, the higher the porosity of the material and the larger the pore size, the greater the adsorption force generated. Through integrated molding of powders of various formulas in different regions, the content of pore-forming agent in the formula and the particle size of low-activity alumina are gradually adjusted from the inner circle to the outer circle, thereby realizing the regulation of the porosity and pore size of each region of the green body after sintering. The porosity of the inner and outer circles of the suction cup can be adjusted in a step-by-step manner within the range of 15-50% and the pore size within the range of 10-100μm, thereby avoiding the problem of easy deformation of the wafer edge due to insufficient edge adsorption.
[0104] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a porous suction cup with a pore gradient distribution, characterized in that: The following steps are involved: (1) Formula powder mixing: 70-90wt% of low-activity alumina powder, 0-15wt% of high-activity alumina powder, 0-15wt% of liquid-phase sintering aid, and 0-30wt% of pore-forming agent are ball-milled to obtain a formula powder for granulation; (2) Powder granulation with glue: Add a binder to the formula powder and mix by ball milling to obtain a slurry, age and homogenize for a period of time, then dry and dehydrate, crush and sieve to obtain the final molding powder; (3) Dry pressing preforming: The two prepared powders are dry pressed into disc-shaped and annular green bodies with nearly uniform thickness and density respectively by using a dry pressing mold; (4) Secondary cold isostatic pressing: The preformed green body is transferred into a mold for assembly and sealing, and then the upper and lower end surfaces are fixed with metal clamps, and the green body is placed in a cold-pressing cylinder for secondary cold-pressing to obtain a green body; (5) Debinding and sintering: The sintering process adopted is the debinding-sintering integrated method. The blank is placed in a sintering furnace for sintering. The sintering temperature is 1500-1550℃ and the heat preservation time is 120-180min. (6) Finishing: The sintered ceramic green body is placed in clarified 58°C low-temperature molten paraffin for pore sealing, and then dewaxed through subsequent processing to obtain the final product.
2. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: In the step (1), the low-activity alumina powder is α-phase low-activity alumina with a particle size of 10-60 μm; the high-activity alumina has a purity of more than 99.95% and a median particle size of 0.1-1.5 μm; the liquid-phase sintering aid used is at least one of silicon dioxide, titanium dioxide and other powders with AR grade purity and a particle size of 1-10 μm; the spherical pore-forming agent used is paraffin micropowder and / or PMMA micropowder with a particle size of 7.5-50 μm.
3. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: The step (1) specifically comprises: firstly adding high-activity alumina powder, liquid-phase sintering aid, and spherical pore-forming agent, and then ball-milling and mixing for 4-8 hours, and then adding large-particle α-phase low-activity alumina powder and continuing ball-milling for 12-24 hours.
4. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: In the step (2), the binder used is a PVA solution with a concentration of 10-15wt%, wherein the PVA has a viscosity of 40-55mPa·s, a degree of alcoholysis of 88%, and a molecular weight of 101200-110000.
5. The method for preparing a porous suction cup with a pore gradient distribution according to claim 4, characterized in that: In the step (2), the amount of PVA solution added is 10-20wt% of the powder mass, the ball ratio of the ball mill is 1:1.5-1:3, the ball milling medium is zirconia ball, the particle size ratio is 1:1-2:1, the small ball diameter is 5-10mm, and the large ball diameter is 15-30mm.
6. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: In the step (2), the slurry aging time is 24-48 hours, the ambient temperature is 20-40°C, and it is dehydrated and dried in a constant temperature and humidity drying oven at 40-60°C and 80-95% humidity for 3-12 hours. The residual moisture content in the final powder is controlled at 3-7%, the glue content is 1-3%, and the powder crushing particle size D50≤150μm and D90≤200μm.
7. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: In the step (3), the dry pressing preforming pressure is 15-30 MPa, the thickness of the two powder preforms is 15-22 mm and the thickness difference does not exceed 0.2 mm, and the green density is 1.39-1.67 / cm 3 .
8. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: The secondary cooling pressure in step (4) is between 180-260 MPa, and the density of the green body after cooling is between 1.88-2.17 g / cm 3 .
9. The method for preparing a porous suction cup with a pore gradient distribution according to claim 1, characterized in that: The sintering temperature of the sintering curve in step (5) is 1500-1550°C, and the heating curve is a sintering process curve: room temperature is increased to 100°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 200°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 250°C at 0.25-0.5°C / min and kept warm for 150-200min, then increased to 350°C at 0.25-0.35°C / min and kept warm for 120-180min, then increased to 350°C at 0.25-0.5 ℃ / min to 450℃ and keep warm for 120-180min, then increase to 600℃ at 0.25-0.5℃ / min and keep warm for 120-180min, then increase to 900℃ at 1-1.5℃ / min and keep warm for 60-90min, then increase to 1200℃ at 1-1.5℃ / min and keep warm for 60-90min, then increase to 1400℃ at 1-1.5℃ / min and keep warm for 60-90min, then increase to 1500-1550℃ at 1-1.5℃ / min and keep warm for 120-240min, then cool with the furnace.
10. A porous suction cup with a pore gradient distribution, characterized in that: The porous suction cup is prepared by the method for preparing a porous suction cup with a pore gradient distribution according to any one of claims 1 to 9, wherein the porosity of the inner and outer circles of the porous suction cup is stepwise controlled within the range of 15-50% and the pore size is within the range of 10-100 μm.
Citation Information
Patent Citations
Electrostatic chuck and electrode sheet for electrostatic chuck
CN101218668A
Gradient metal-based porous material and preparation method and application thereof
CN110732672A
Porous vacuum chuck and preparation method thereof
CN112407936A
Preparation method of porous ceramic with controllable aperture and porosity
CN118684516A
Alumina porous ceramic material as well as preparation method and application thereof
CN118724565A
Cited By
Vacuum chuck with gradient aperture and manufacturing method and application thereof
CN121322519A